PEMBELAJARAN KOOPERATIF NUMBERED HEAD TOGETHER UNTUK PENINGKATAN HASIL BELAJAR IPS - Atut Dwi Sartika; Pargito Pargito; Sumardi Sumardi (Indonesia Journal of Educational Technology, 2013)
This study aims to analyze: (1) measures of learning, (2) the implementation process of learning, (3) learning evaluation system, (4) improved learning outcomes IPS class VII Secondary School District 8 Metro with cooperative learning Numbered Heads Together. Research using action research with three cycles, the first cycle of cooperative learning with LKS NHT, NHT second cycle of cooperative learning by using media images and worksheets, third cycle NHT type of cooperative learning, media images and teaching materials in the form of a summary of the material with LKS. The collection of data through observation and tests competency test and quantitatively analyzed descriptively.The results: 1) design lesson plans with worksheets with syntax NHT: NHT learning with worksheets at the start by forming a study group consists of 4 members of each group to determine the serial number of each member, the student forming discussion groups according to the rules / criteria of cooperative learning groups in NHT with LKS, guiding teacher study groups, student worksheets and assignment in active discussions, the teacher said the serial number on a randomized group, students answer according to the specified number of teachers, the students were able to present the results of individual and group discussions, teachers with students making inferences. 2) student learning activities of ten defined criteria, there are four of the most prominent activity is the ability to ask, dare express opinions, give feedback bold, daring to present observations and discussions. 3) evaluation of learning through teaching Social Sciences NHT implemented via compile phase grating problem, fill out a card problem, create test questions, and conduct tests students' mastery of skills indicators that have been learned. From the results of absorption tests indicate the end of each cycle there is an increase from cycle to cycle. 4) The results of student learning has increased, the first cycle to the second cycle of student learning outcomes increased by 9.67 from 48.39% in the first cycle to 58.06%, while from the second cycle to third cycle increased by 25.81%, from 58.06% in the second cycle to 83.87% in the third cycle, it shows more than 80 the number of students achieving a landslide victory over the completeness indicator.Penelitian ini bertujuan untuk menganalisis (1) langkah-langkah pembelajaran. (2) proses pelaksanaan pembelajaran. (3) sistem evaluasi belajar. (4) peningkatan hasil belajar IPS siswa kelas VII Sekolah Menengah Pertama Negeri 8 Metro dengan pembelajaran kooperatif Numbered Heads Together. Penelitian menggunakan penelitian tindakan dengan 3 siklus, pada siklus pertama pembelajaran kooperatif NHT dengan LKS, siklus kedua pembelajaran kooperatif NHT dengan menggunakan media gambar dan LKS, siklus ketiga pembelajaran kooperatif tipe NHT, media gambar dan bahan ajar berupa ringkasan materi disertai LKS. Pengumpulan data menggunakan observasi dan tes uji kompetensi, dan dianalisis secara deskriptif kuantitatif. Hasil penelitian: 1) desain RPP NHT disertai LKS dengan sintak: pembelajaran NHT disertai LKS di awali dengan membentuk kelompok belajar berjumlah 4 anggota tiap kelompok dengan menentukan nomor urut masing-masing anggota, siswa membentuk kelompok diskusi sesuai aturan/kriteria kelompok dalam pembelajaran kooperatif NHT disertai LKS, guru membimbing kelompok belajar, siswa mengerjakan tugas pada LKS dan berdiskusi secara aktif, guru menyebutkan salah satu nomor urut pada kelompok secara acak, siswa menjawab sesuai nomor yang ditentukan guru, siswa mampu mempresentasikan hasil diskusi secara individu dan kelompok, guru bersama siswa membuat kesimpulan. 2) aktivitas belajar siswa dari sepuluh kriteria yang ditetapkan, terdapat empat aktivitas yang paling menonjol yaitu kemampuan bertanya, berani mengemukakan pendapat, berani memberikan tanggapan, berani mempresentasikan pengamatan dan diskusi. 3) evaluasi pembelajaran Ilmu Pengetahuan Sosial melalui pembelajaran NHT dilaksanakan melalui tahap menyusun kisi-kisi soal, mengisi kartu soal, membuat soal tes, dan melaksanakan tes kemampuan siswa tentang penguasaan indikator-indikator yang telah dipelajarinya. Dari hasil tes daya serap setiap akhir siklus menunjukkan ada peningkatan dari siklus ke siklus. 4) Hasil belajar siswa mengalami peningkatan, siklus pertama ke siklus ke dua hasil belajar siswa mengalami peningkatan sebesar 9,67 dari 48,39% pada siklus pertama menjadi 58.06% Sedangkan dari siklus kedua ke siklus ketiga mengalami peningkatan sebesar 25,81%, dari 58,06% pada siklus ke dua menjadi 83,87% pada siklus yang ketiga, hal tersebut menunjukkan lebih dari 80 jumlah siswa telak mencapai hasil di atas indikator ketuntasan.Kata kunci: hasil belajar IPS, kooperatif NHT